# 1. Solve the following for x.

3-(x+(-4))= 2x-6+5x

I figured that the answer is no solution. Is this correct?

I have been working with my friend on this next problem and neither of us know which is correct.

2. Solve for r. I=P(1+rt)

The first answer is I-P/Pt=r.

The second answer is I-1P/t=r.

Are either of these answers correct?

## 1. Solve the following for x.

3-(x+(-4))= 2x-6+5x

**remove innner parentheses.
3-(x-4)=2x-6+5x
remove next set of parentheses.
3-x+4=2x-6+5x
combine terms on left and right,
7-x=7x-6
move numbers to right and xs to left.
-x-7x=-6-7
combine terms.
-8x=-13
Multiply through by -1
8x = 13
x=13/8**

I figured that the answer is no solution. Is this correct?

I have been working with my friend on this next problem and neither of us know which is correct.

2. Solve for r. I=P(1+rt)

The first answer is

**I-P/Pt=r**.

**This one is correct.**

The second answer is I-1P/t=r.

Are either of these answers correct?

## Check my work.

## To solve the equations you provided:

1. Solve the following for x:

3 - (x + (-4)) = 2x - 6 + 5x

To find the value of x, we need to simplify and combine like terms on both sides of the equation. First, let's simplify the left side by removing the parentheses:

3 - (x + (-4)) becomes 3 - (x - 4)

Since you have a negative sign before the parentheses, you need to distribute the negative sign to both terms inside:

3 - (x - 4) becomes 3 - x + 4

Simplifying further:

3 - x + 4 = 2x - 6 + 5x

Combine like terms on both sides:

7 - x = 7x - 6

Now, let's isolate all the terms containing x to one side of the equation. We can do this by adding x to both sides:

7 - x + x = 7x - 6 + x

7 = 8x - 6

Next, let's isolate the term with x by moving the constant term (-6) to the other side of the equation. We can do this by adding 6 to both sides:

7 + 6 = 8x - 6 + 6

13 = 8x

Finally, divide both sides by 8 to solve for x:

13/8 = x

So, the solution to the equation is x = 13/8.

Therefore, your initial assumption of "no solution" is incorrect.

2. Solve for r in the equation I = P(1 + rt):

To find the value of r, we need to isolate it on one side of the equation. Let's start by distributing the term rt to simplify the equation:

I = P + Prt

Now, let's isolate the term containing r by subtracting P from both sides:

I - P = Prt

To solve for r, we need to divide both sides of the equation by Pt:

(I - P) / Pt = r

So, the correct answer is:

r = (I - P) / Pt

The first answer you provided, I - P/Pt = r, is incorrect because you need to subtract P from I before dividing by Pt.

The second answer you provided, I - 1P/t = r, is also incorrect as it has a misplaced negative sign and incorrect multiplication (1P instead of just P and t instead of Pt).

Therefore, the correct answer is r = (I - P) / Pt.